2004
DOI: 10.1111/j.1467-856x.2004.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Thinking About Making a Difference

Abstract: This article works across disciplines: politics, geography and social and cultural theory. Issues of space and body are brought to bear on how we think about the question 'making a difference'. By considering difference in terms of the socio-spatial impact of the presence of hitherto socially excluded groups, such as women and racialised minorities, the gendered and racialised nature of the body politic and most specifically its 'elite' positions is brought into focus. The co-existence of women and 'black' and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Female children, adolescent girls, and adult women report exposure to sexually degrading jokes, being sexually harassed, being called sexual names, having body parts ogled, and being the target of unwanted sexual advances to a significantly greater degree than boys and men (Gardner, 1980;Hill & Fischer, 2008;Klonoff & Landrine, 1995;Kozee, Tylka, Augustus-Running head: OBJECTS AND ACTIONS Horvath, & Denchik, 2007;Macmillan, Nierobisz, & Welsh, 2000;Moradi, Dirks, & Matteson, 2005;Murnen & Smolak, 2000;Puwar, 2004;Swim, Hyers, Cohen, & Ferguson, 2001). Media encounters include the depiction of women as primarily bodies and body parts in magazines, advertisements, TV programming, film, music lyrics and videos, and internet and social networking sites (for reviews, APA, 2007;Calogero, Tantleff-Dunn, & Thompson, 2011;Reichert & Carpenter, 2004).…”
mentioning
confidence: 99%
“…Female children, adolescent girls, and adult women report exposure to sexually degrading jokes, being sexually harassed, being called sexual names, having body parts ogled, and being the target of unwanted sexual advances to a significantly greater degree than boys and men (Gardner, 1980;Hill & Fischer, 2008;Klonoff & Landrine, 1995;Kozee, Tylka, Augustus-Running head: OBJECTS AND ACTIONS Horvath, & Denchik, 2007;Macmillan, Nierobisz, & Welsh, 2000;Moradi, Dirks, & Matteson, 2005;Murnen & Smolak, 2000;Puwar, 2004;Swim, Hyers, Cohen, & Ferguson, 2001). Media encounters include the depiction of women as primarily bodies and body parts in magazines, advertisements, TV programming, film, music lyrics and videos, and internet and social networking sites (for reviews, APA, 2007;Calogero, Tantleff-Dunn, & Thompson, 2011;Reichert & Carpenter, 2004).…”
mentioning
confidence: 99%
“…While it is clear that the Minister's unpopularity in the Northern Ireland Assembly is attributable to a complex range of factors including her policies, ideological and political stance, and her interactional style, it is clear that it is the way she draws upon gendered discursive resources significantly contributes to her unpopularity. Women in parliamentary institutions must 'manage their femininity carefully' because if they do not display the acceptable feminine style in these incredibly gendered environments, they risk being labelled as somewhat strange and grotesque' [50]. It is possible that the wider political contexts of Nationalism and the symbolic use of Irish language characteristic of this Community of Practice align the Minister more strongly with the discourse of resistance and opposition, and this makes her less inclined or able to draw upon facilitative styles.…”
Section: Conclusion and Discussion Of Findingsmentioning
confidence: 99%
“…Previous sociolinguistic research on House of Commons debates has found that although women participate equally with men in terms of the formal or 'legal' debate rules, they do not participate equally in terms of illegal debate discourse (by contributing 'out of turn', for example) [1][2]. The reasons for this are likely to be complex, and related in part to the 'visibility' of women in a traditionally male-dominated forum [3] and the nature of traditional parliaments as a 'linguistic habitus' [4] in which 'silence or hypercontrolled language' is imposed on some people, while others are allowed the 'liberties of a language that is securely established' [5]. Traditional parliaments can therefore be viewed as a 'gendered space' in which the setting and the communicative tasks together become an index of a gendered style.…”
Section: Introductionmentioning
confidence: 99%
“…The potency of this male-gendered way of 'doing' politics is so strong as to be assumed as the universal norm for political activity, contributing to a notion of men as 'natural leaders' (Duerst-Lahti, 2002, 2008. Women entering politics are contrasted against the 'naturalised' male inhabitants (Puwar, 2004). Their presence is queried and behaviour scrutinised, which, in turn, contributes 'to a notion of women as out of place and unnatural in the political sphere' (Falk, 2010, p. 37;Puwar, 2004).…”
Section: Supplymentioning
confidence: 99%
“…Women entering politics are contrasted against the 'naturalised' male inhabitants (Puwar, 2004). Their presence is queried and behaviour scrutinised, which, in turn, contributes 'to a notion of women as out of place and unnatural in the political sphere' (Falk, 2010, p. 37;Puwar, 2004).…”
Section: Supplymentioning
confidence: 99%